Edukasi Pasar Modal: Meningkatan Literasi Dan Inklusi Keuangan Melalui Pemahaman Pasar Modal - Armadani Armadani; Nurhayati Lubis; Liza Ulfiana; Nurhayanti Nurhayanti; M. Wahyu Pratama Putra; Lita Arfah (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2026)
The level of literacy and inclusion of the Indonesian public regarding capital markets remains very low. Not only among the general public, but the phenomenon of low financial knowledge and practices related to capital markets also remains a problem among academics, both students and lecturers. The purpose of this community service activity is to improve literacy and inclusion in the community, especially among students and lecturers on the campus of Al-Kifayah Islamic University, Riau. The method used was a workshop with material presentations and a question and answer session. The results of this service are an increase in understanding and practice of capital markets on campus. Furthermore, during the workshop, an agreed follow-up was the implementation of a capital market school to further deepen understanding in the future